Karen Fog Olwig: FÆLLESSKABETS BEGRAVELSE? - Olwig, Karen Fog (Tidsskriftet Antropologi, 2004)
Oprindelse og forbundethed blandt caribiske migranter Migration studies seem to have created a “hybrid” research object, defined both thematically (as a category of people affected by migration) and in terms of cultural background (as a group of people belonging to a particular “diasporic” community by virtue of their shared place of origin). Through an ethnographic analysis of the funeral of a Caribbean migrant to England, the article shows that the burial ritual created an arena for the creation, demarcation and contestation of several different, partially overlapping communities. This points to the need to explore the concrete expressions of moral values and obligations, of social notions and practices of relatedness and of cultural identification and recognition that unite and divide particular groups of people of migratory background. At a more general level, it underlines the need to deconstruct the conflation of the category of migrants and their descendants with diasporic communities of belonging rooted in a distant place of origin.